Beta fuzzy logic systems: Approximation properties in the MIMO case - Alimi, Adel M.; Hassine, Radhia; Selmi, Mohamed (Zielona Góra: Uniwersytet Zielonogórski)
Many researches have been interested in the approximation properties of Fuzzy Logic Systems (FLS), which, like neural networks, can be seen as approximation schemes. Almost all of them tackled the Mamdani fuzzy model, which was shown to have many interesting approximation features. However, only in few cases the Sugeno fuzzy model was considered.
Keywords: Beta function; universal approximation property; best approximation property; interpolation property; Sugeno fuzzy model; MIMO systems